Cathelicidin Antimicrobial Peptide Levels in Atherosclerosis and Myocardial Infarction in Mice and Human - Höpfinger, Alexandra; Schmid, Andreas; Karrasch, Thomas; Pankuweit, Sabine; Schäffler, Andreas; Grote, Karsten; Justus Liebig University Giessen (My University, 2024)
Obesity represents a worldwide health challenge, and the condition is accompanied by elevated risk of cardiovascular diseases caused by metabolic dysfunction and proinflammatory adipokines. Among those, the immune-modulatory cathelicidin antimicrobial peptide (human: CAMP; murine: CRAMP) might contribute to the interaction of the innate immune system and metabolism in these settings. We investigated systemic CAMP/CRAMP levels in experimental murine models of atherosclerosis, myocardial infarction and cardiovascular patients. Atherosclerosis was induced in low-density lipoprotein receptor-deficient (Ldlr−/−) mice by high-fat diet (HFD). C57BL/6J wild-type mice were subjected to myocardial infarction by permanent or transient left anterior descending (LAD)-ligation. Cramp gene expression in murine organs and tissues was investigated via real-time PCR. Blood samples of 234 adult individuals with or without coronary artery disease (CAD) were collected. Human and murine CAMP/CRAMP serum levels were quantified by ELISA. Atherosclerotic mice exhibited significantly increased CRAMP serum levels and induced Cramp gene expression in the spleen and liver, whereas experimental myocardial infarction substantially decreased CRAMP serum levels. Human CAMP serum quantities were not significantly affected by CAD while being correlated with leukocytes and pro-inflammatory cytokines. Our data show an influence of cathelicidin in experimental atherosclerosis, myocardial infarction, as well as in patients with CAD. Further studies are needed to elucidate the pathophysiological mechanism.
Keywords: ddc:610